UKRIDA HOSPITAL WORKERS STRESS PROFILE USE PERCEIVED STRESS SCALE AND HEART RATE VARIABILITY METHODS - Ronald Winardi Kartika; Fira Sonia; Chrispian Mahmudi; Hartanto; Yosephin Sri Sutanti (Berkala Ilmiah Kedokteran Duta Wacana, 2023)
Background Stress is a condition of unbalance the physical and mental states, unable to respond of stimulus situations, and the end cause stress responses. Stress is one of the fourth ranked diseases in the world that experience stress. The symptoms of stress are palpitations, headaches, high blood pressure, disturbed digestion, shortness of breath, and difficulty sleeping. The measuring of stress using the perceived stress scale questionnaire in which the questionnaire has ten questions and the results obtained can determine the level of stress. If stimulation from internal or external stress occurs, will affect the nervous system, a heart rate variability tool used to measure the level of stress. Objective The aims of this study are to determine the relationship between stress and heart rate variability, and stress levels based on gender and age. Methods The conducted study was with quantitative analysis methods using cross-sectional design on 262 data. Results Based on the results of this study, the majority were aged less than thirty-five years and there were more women than men. In addition, the results of the chi-square test showed no significant relationship between stress and heart rate variability because the results of significancy was 0,432. Conclusions Measurement of stress on UKRIDA Hospital workers has not shown a significant relationship between the stress questionnaire and heart rate variability. However, there was a tendency for the worker to experience stress accompanied with an increase of the sympathetic nervous system measured by the Heart Rate Variability methods.